On the Causes of the Deaths of Burgesses and Noblemen in the Early Modern Period in Upper Hungary - Covan Miroslav (Acta Medica Martiniana)
The present study intends to highlight the hitherto underused sources concerning the history of medicine. These are archival materials of various kinds, but also artefacts of a funerary nature known as sepulchral monuments. In his research activities aimed at the study, analysis and translation of medieval and early modern Latin texts, the author of this paper has also examined a wide variety of writings containing references to the causes of death of individuals from the ranks of the nobility as well as the common bourgeoisie. The narrative quality of these historical sources has varied. Only extensive archival research will make it possible to draw conclusions about the greater or lesser usefulness of medieval and early post-medieval archival material for the history of medicine, specifically in uncovering the causes of death of individuals in our territory during this period. For the purposes of the present study, we proceeded to a selective choice of those written sources in which the presumption of new discoveries was most probable. From the territorial point of view, we focused on the region of present-day eastern Slovakia due to the preservation of numerous relevant archival and other documentary sources.